Seorang Perempuan Perokok Tembakau dan Mariyuana dengan Pneumotoraks Spontan Primer Akibat Blep Multipel yang Pecah: [Spontaneous Primary Pneumothorax in a Woman: Smoke and Cannabis Dual Harm] - Yenny Kusmatuti; Isnin Anang Marhana (Faculty of Medicine Universitas Airlangga, 2015)
Background: Primary spontaneous pneumothorax (PSP) can be caused by a ruptured blep emfisematus subpleural. People who smoke tobacco and marijuana simultaneously arise PSP will be more risky than just smoking tobacco. Pneumothorax in cannabis smokers may occur due to coughing at the time was holding their breath, when they were smoking marijuana. Case: We report the case of 33-year-old woman with recurrent shortness of breath as a result of primary spontaneous pneumothorax in the right hemithorax. The patient’s tobacco and marijuana smokers. Patients had undergone previous pleurodesis. Chest X-ray picture of the lines conveniently indicates lung collapse and air-fluid level in the right hemithorax. Thoracoscopic showed a large bronchopleural fistula. During thoracotomy found one bronkopeural fistula, three large blep, and more than 15 small blep. Then do the suturing of fistula and blep. Patients recover in a short time and in good condition during treatment. Conclusion: Tobacco and marijuana smoking is a risk factor that is synergistic to the occurrence of primary spontaneous pneumothorax. These patients consume both are irregular but have resulted in multiple blep that can rupture and cause a pneumothorax.